2017
DOI: 10.1097/ico.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Breakthrough Haze After Photorefractive Keratectomy With Mitomycin C: Incidence and Risk Factors

Abstract: Hyperopic and large myopic or astigmatic corrections carry higher risk of haze. Longer MMC application might have beneficial haze prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 39 publications
0
44
0
8
Order By: Relevance
“…After surface ablation, up to 52% of eyes develop some degree of corneal haze in the first months, with values most often reported within the range of 5%–20% 18. The overall incidence of haze is higher in eyes treated for hyperopia than for myopia 19. Wagh et al reported a 40% incidence of remnants of the haze ring still evident 18 years after hyperopic PRK, but MMC was not used when the procedures were performed 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After surface ablation, up to 52% of eyes develop some degree of corneal haze in the first months, with values most often reported within the range of 5%–20% 18. The overall incidence of haze is higher in eyes treated for hyperopia than for myopia 19. Wagh et al reported a 40% incidence of remnants of the haze ring still evident 18 years after hyperopic PRK, but MMC was not used when the procedures were performed 4.…”
Section: Discussionmentioning
confidence: 99%
“…Second, chilled balanced salt solution was used throughout the surgery. Population-based factors specific to our cohort (comprising adults living in Central Europe), such as relatively low ultraviolet light exposure, may also play a role 19. Finally, the modern excimer laser used in the study could also be an influencing factor, as the final 20% of ablation was performed with a low energy fluence, potentially providing smoother ablation surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the risk of corneal haze increases 2 fold in subjects with more than 6 D myopia. 9 This should be considered an important limitation, and more homogeneous groups of patients in a narrower age range and separated into groups of low, moderate, or high myopia would be able to refine the results and overcome this limitation. Epithelial healing (re-epithelialization) processes and subjective visual parameters (pain, photophobia, photic phenomena, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Mitomycin C 0.02% was applied for 30 seconds in eyes with SE greater than 3 D and for 60 seconds if greater than 6 D due to increased risk of corneal haze. 9 After laser ablation, a bandage contact lens (Senofilcon A [Acuvue Oasys, J&J, Vision Care, Inc., Jacksonville, FL]) was applied for 5 days. Postoperative topical moxifloxacin 0.5% (Vigamox, Alcon, Fort Worth, TX) 3 times a day for 1 week, topical dexamethasone (Maxidex, Alcon, Fort Worth, TX) starting after epithelial healing and tapered off over 3 weeks and artificial tears every 2 hours for 2 months were prescribed.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Über die Dauer der Mitomycin-C-Applikation existiert keine einheitliche Empfehlung, wir haben uns in dieser Studie für eine relativ kurzzeitige Applikationzeit (30 s) entschieden. Eine Korrelation der Haze-Wahrscheinlichkeit mit der Applikationsdauer von Mitomycin C ist beschrieben [11]. Andererseits führt eine verlängerte Mitomycin-C-Applikationsdauer auch zum Übertritt des Wirkstoffes ins Kammerwasser und könnte endothelschädigend wirken [12].…”
Section: Diskussionunclassified